Information and analytical support of the education quality management system - Baranenko, R.; Sokol, H.; Pustovoitov, P.; Zakharov, R. (Полтавський національний технічний університет ім. Юрія Кондратюка, 2023)
The article analyzes the problem of informational and analytical provision of the education quality management system. The purpose of the article is to determine the role of modern information technologies in the process of improvement and modernization of the educational system. The components of the information system of quality management, which is defined as a set of interconnected or interacting elements of the organization for the development of policies and goals, as well as processes for achieving goals in the field of education quality, have been studied. It is proven that the formalized information system of education quality management creates a basis for planning, implementation, monitoring and improvement of education quality management activities.

У статті аналізується проблема інформаційно-аналітичного забезпечення системи управління якістю освіти. Метою статті є визначення ролі сучасних інформаційних технологій у процесі вдосконалення та модернізації системи освіти. Досліджено компоненти інформаційної системи управління якістю, яка визначається як сукупність взаємопов'язаних або взаємодіючих елементів організації для розробки політики та цілей, а також процесів досягнення цілей у сфері якості освіти. Доведено, що формалізована інформаційна система управління якістю освіти створює основу для планування, реалізації, моніторингу та вдосконалення діяльності з управління якістю освіти.
Інформаційно-аналітичне забезпечення системи управління якістю освіти
Keywords: information system; information technologies; quality of education; quality management; інформаційна система; інформаційні технології; якість освіти; управління якістю